DEVELOPMENT AND APPLICATION OF A WATER SERVICE AND QUALITY SUSTAINABILITY INDEX IN THE MUNICIPALITIES OF THE PCJ BASIN - Guedes, Walef Pena; Ferreira, Denise Helena Lombardo [UNESP]; Sugahara, Cibele Roberta (Univ Estadual Paulista Julio Mesquita Filho, 2024)
Currently, ensuring water in adequate quantity and quality is an urgent concern, highlighting the need for sustainable management of water resources. In this process, the use of comprehensive indicators and the development of new indicators play a crucial role. The present research aims to propose a Sustainability Index for Water Supply and Quality for all municipalities within the Piracicaba, Capivari, and Jundia & iacute; River Basins. Methodologically, exploratory and explanatory research was conducted, employing a qualitative-quantitative approach and case study, supported by multivariate analysis. The Piracicaba, Capivari, and Jundia & iacute; River Basins were chosen as the study's focus due to their significant influence on the region, as well as their substantial economic and demographic activities. Data were collected for the ten indicators of the National Sanitation Information System for the year 2021. With the consolidation of the dataset for the selected indicators, it was possible to apply the multivariate technique of factor analysis, and from the factor scores, construct the Sustainability Index for Water Supply and Quality, followed by the ranking of the observations. The results suggest that the region faces complex challenges regarding water supply and quality for a large part of the municipalities, especially concerning the effects of water stress in certain basins. Moreover, it was possible to identify that the municipalities of Campinas, Piracicaba, and Americana stand out with the best indices, in contrast to Corumbata & iacute;, Monte Alegre do Sul, and Rio das Pedras, which present the greatest challenges.
Keywords: Water service; Water quality; Sustainability indicators; Indicators; PCJ basins